Association Between Diabetic Retinopathy and Cognitive Impairment: A Systematic Review and Meta-Analysis - Cheng, Dihe; Zhao, Xue; Yang, Shuo; Wang, Guixia; Ning, Guang (Frontiers in Aging Neuroscience, 2021)
Diabetic retinopathy (DR) is one of the most common microvascular complications associated with diabetes mellitus. However, its correlation with another diabetes-related disorder, cognitive impairment, has not been well studied. This systematic review and meta-analysis aimed to explore the association between DR and cognitive impairment. MEDLINE (PubMed), the Cochrane Library, and EMBASE databases were searched for observational studies that reported an association between DR and cognitive impairment. Data from selected studies were extracted, and a meta-analysis was conducted using fixed-effects modeling. Fifteen observational studies were included in the systematic review, and 10 studies were included in the meta-analysis. The odds ratio of the association between DR and cognitive impairment was 2.24 (95% confidence interval [CI], 1.89-2.66; I2 = 0.8%). The hazard ratio of the association between DR and cognitive impairment was significant in four studies, ranging from 1.09-1.32. Minimal or mild DR was not significantly associated with cognitive impairment (odds ratio [OR], 2.04; 95% CI, 0.87-4.77). However, the association between proliferative DR and cognitive impairment (OR, 3.57; 95% CI, 1.79-7.12; I2 = 16.6%) was not stronger than the association between moderate or worse DR and cognitive impairment (OR, 4.26; 95% CI, 2.01-9.07; I2 = 0.0%). DR is associated with cognitive impairment, and screening for DR will be helpful for the early identification of individuals with cognitive impairment. Further studies are needed to confirm the association between proliferative DR and cognitive impairment.